The YellowPress Periodical : #1 : October 2014 : Sint Lucas Antwerpen. - Crombez, Thomas; Van Gerrewey, Christoph; Gorus, Kim; Heirwegh, Ward (Antwerpen : KdG / Sint Lucas Antwerpen, 2014)
Marc Nagtzaam: The Aesthetic of the Fragment ; Wesley Meuris: Research Building ; Dirk De Backer: 'Je penserai toujours à toi' Congo +suprematisme ; Afterschool Make Me ( )
boek